Efektivitas antibakteri ekstrak daun sirih (Piper betle Linn)terhadap bakteri Enterococcus faecalis (Antibacterial effectiveness of betel leaf extract (Piper Betle Linn) to Enterococcus faecalis) - Armianty Armianty; Indrya Kirana Mattulada (Journal of Dentomaxillofacial Science, 2014)
Enterococcus faecalis is one of bacteria which have resistance against the pulp tissue defense mechanism and oftenfound in endodontic infections. This bacterial is may hold good colonization, can survive in the root canal withoutother bacteria, and is capable of producing toxins directly or through the induction of inflammation. Betel leaf (Piperbetle Linn)contain essential oils, as the main components of the essential oils are phenols and compounds, amongother derivate such as kavikol compound that has bactericidal five times stronger than phenol. Phenol disrupts threedimensional structure of the bacterial protein to be a random structure and denatured protein, and damages biologicalactivity. Chlorhexidine has been shown to be effective against Enterococcus in the root canal irrigation. Betel leaf canbe chosen as an alternative material root canal irrigation saline. This in vitro experimental laboratory study is aimedto determine the effectiveness of anti-bacterial extracts of betel leaf for E.faecalis bacteria. The minimum inhibitoryconcentration of betel leaf extract is determined by observing the lowest concentration that was first seen clearly,namely 20%. The assay method of these anti-bacterial effect used diffusion method to comparing the inhibition zonebetel leaf extract solution in concentration of 20% be compared 0.2% chlorhexidine, 2% chlorhexidine, and distilledwater. Each group performed eight times repetition respectively. Data analysis used one way anova test followed byLSD test. From this research, it was concluded that 2% chlorhexidine has antibacterial effect for E.faecalis better thanbetel leaf extract and 0.2% chlorhexidine.